Machine Learning for Cyber Security: Third International Conference, ML4CS 2020, Guangzhou, China, October 8-10, 2020, Proceedings, Part II - Chen, Xiaofeng; Yan, Hongyang; Yan, Qiben; Zhang, Xiangliang (Lecture Notes in Computer Science, 2020)
This three volume book set constitutes the proceedings of the Third International Conference on Machine Learning for Cyber Security, ML4CS 2020, held in Xi'an, China in October 2020.The 118 full papers and 40 short papers presented were carefully reviewed and selected from 360 submissions. The papers offer a wide range of the following subjects: Machine learning, security, privacy-preserving, cyber security, Adversarial machine Learning,  Malware detection and analysis,  Data mining, and  Artificial Intelligence.